Interpretation of atomic friction experiments based on atomistic simulations - Maier, Sabine; et al. (Journal of Vacuum Science & Technology B, 2007)
Atomic stick-slip experiments on the KBr(100) surface are analyzed using classical zero temperature atomistic simulations. Three different tip models exhibiting atomic stick-slip movement are studied in comparison with the experimental data and the Tomlinson model. The implications of a compliant tip apex for the stick-slip process and the dissipation pathways are discussed. © 2007 American Vacuum Society.
Created from Fastlane, Scopus look-up